Patients' perspective of a dedicated biologic clinic for inflammatory arthritis. Issue 5 (10th June 2019) - Cefai, Erika; Balzan, Daniela; Mercieca, Cecilia; Borg, Andrew
Abstract : Purpose: The purpose of this paper is to assess the patient's perspective on a dedicated clinic set up for patients diagnosed with an inflammatory arthritis who are being treated with a biologic. It proposes that dedicated clinics offer better overall care. The aim of this quality improvement survey is to evaluate the level of patient satisfaction with this clinic and identify any unmet needs. Design/methodology/approach: This study was based on a quality improvement survey, which was developed using Zineldin's five qualities model and assessed various aspects pertaining to service quality and improvement. A structured interview approach was used and 44 consecutive patients were recruited. Findings: This paper explores key aspects that influence patient satisfaction within a rheumatology outpatient setting such as education on arthritis and biologics and involvement in decision making. It provides insight on what patients value most and it also addresses organizational aspects that can have an impact on patient satisfaction. It suggests that service quality can be linked to the degree of patient satisfaction. Research limitations/implications: Direct interviewing of patients could have introduced a source of bias whilst questions are being answered. On the other hand, it provided an opportunity to clarify instantly any doubts and therefore avoiding any inadvertent errors. Practical implications: This paper reinforces that specialized clinics enable the caring rheumatologist to provide better care for patients on biologics. Service providers should continue developing their services around the patient's needs and perspectives in order to continue improving the service. Social implications: Dedicated biologic clinics allow more judicious monitoring of patients who are taking these highly efficacious but costly medications. Originality/value: This survey has reinforced that patients highly value dedicated clinics. These results strengthen the case that healthcare services should continue investing on specialized clinics.